Acute cytotoxicity test of PM2.5, NNK and BPDE in human normal bronchial epithelial cells: A comparison of a co-culture model containing macrophages and a mono-culture model. (December 2022) - Zhou, Jiaxin; Zou, Hongxing; Liu, Yongqin; Chen, Yuyang; Du, Yiheng; Liu, Jiayu; Huang, Zhaowen; Liang, Linlin; Xie, Rui; Yang, Qiaoyuan
Abstract: Background: Based on extensive research on cytotoxicity of exogenous compounds in vitro, it is essential to develop a cell model that better mimics environment in vivo to explore cytotoxic mechanisms of exogenous compounds. Methods: A co-culture system was established using a transwell system with Beas-2B and U937 cells. Cells were treated with fine particulate matter (PM2.5; 25, 50 and 100 μg/mL), nicotine-derived nitrosamine ketone (NNK; 50, 100 and 200 μg/mL) and benzo( a )pyrene diol epoxide (BPDE; 0.5, 2 and 8 μM) for 24 h. Cell proliferation, apoptosis and cell cycle, DNA damage were detected by CCK-8 and EdU, flow cytometry, and comet assay, respectively. Differentially expressed transcript and cytokine concentrations were determined by transcriptome sequencing and Cytokine Array, respectively. Results: Compared with mono-culture, cell proliferation increased, apoptosis decreased, and DNA damage decreased in a dose-response relationship in co-culture. Gene expression profile was significantly different in co-culture, with significantly increased expression levels of 48 cytokines in co-culture. Conclusion: Cytotoxic damage to Beas-2B cells induced by exogenous carcinogens, including PM2.5, NNK and BPDE, was significantly reduced in a co-culture system compared with a mono-culture system. The mechanism may be related to changes in expression of cytokines, such as LIF, and activation of related pathways, such as TNF signaling pathway. Cytotoxic damage to Beas-2B induced by PM2.5, NNK and BPDE, was significantly reduced in co-culture. The mechanism may be related to changes in expression of cytokines and activation of related pathways. These findings provide new insights into cytotoxicity and experimental basis for safety evaluations of exogenous carcinogens. Highlights: Toxicity evaluation was different between mono-culture and co-culture. The toxicity of PM2.5, NNK and BPDE decreased under co-culture condition. Difference effects may be related to cytokines expression and pathways activation.